Music Copyright Protection in the Indonesian TikTok Era - Boy Gabriel Yohanes; Revianty Yovinka; Yossi Niken Respati Artin Soediarto (Journal of Law, Politic and Humanities, 2026)
The development of digital technology has transformed the patterns of music consumption and distribution globally, including in Indonesia. Short-video–based social media platforms such as TikTok have become spaces for creative expression while simultaneously posing serious challenges to the protection of music copyright. The widespread use of unlicensed song clips, remixes, and viral cover versions on TikTok reflects the weakness of digital law enforcement, even though Indonesia normatively possesses a comprehensive legal framework through Law Number 28 of 2014 on Copyright, Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions, and other implementing regulations. This research intends to examine Indonesia's regulations regarding music copyright protection on the TikTok platform and to evaluate how well these rules are applied in real situations. The study uses a standard legal approach that includes statutory, conceptual, and literary methods. It involves qualitatively examining primary and secondary legal resources through legal interpretation. The findings indicate that music copyright protection in Indonesia is normatively established and covers moral rights, economic rights, as well as civil, criminal, and administrative sanctions. However, its practical effectiveness remains limited due to reliance on manual reporting mechanisms (notice and takedown), the absence of regulations on automatic detection systems, and weak inter-agency coordination among the Directorate General of Intellectual Property, the Ministry of Communication and Digital Affairs, and the National Collective Management Organization. This study concludes that adaptive legal policy reforms are necessary through the implementation of technological enforcement, integration of national digital systems, and the enhancement of public legal literacy to strengthen copyright protection in the digital era.